Penyelesaian Sengketa Tanah Hak Ulayat Masyarakat Suku Kajang dengan PT.PP London Sumatera Indonesia di Kabupaten Bulukumba" - Amiruddin Amiruddin (PETITUM, 2014)
The result of the study, found in effectiviness settlement throught litigation (Indonesian Supreme Court Verdict) and non litigation, because of the law, law enforcement, community.infrastructure and culture. In addition, because the mediator is not independent. Due to the completion of the settlement of the dispute led to the failure of the rule of law and the emergence of social phenomena.